The effectiveness of weight training and stretching ("PNF") on the balance of muscles moving the knee and foot joints and its effect on some motor and skill abilities of volleyball players - Hussein Ibrahim Al-Ajouri, Mohammed (sports creativity, 2025)
This study aimed to identify the effectiveness of weight training and prolongation "PNF" the balance of the muscle dynamics of articular knee, foot and its impact on some motor abilities and skills of volleyball players, and to reach results, the researcher designed a program of strength using weights, and prolongation using the method of "PNF" works to restore balance muscle of the muscles holding the extensor joints, was also tested each of the "power, ability, fitness, prolongation, speed, beating offensive, bulwark" and applied research on a sample intentionally included (9) players to volleyball from the higher levels, the researcher concluded that improving the balance muscle works to raise the level of motor skills of volleyball players and then skills "under discussion", where the percentage of improvement in power 14.1%, and motor skills 14.5%, and skills 21.8%, and the researcher recommends using exercise weights and prolongation "PNF" are regulated to restore the imbalance on the articular knee and foot.